2005
DOI: 10.1172/jci22232
|View full text |Cite
|
Sign up to set email alerts
|

PKCλ regulates glucose-induced insulin secretion through modulation of gene expression in pancreatic β cells

Abstract: Altered regulation of insulin secretion by glucose is characteristic of individuals with type 2 diabetes mellitus, although the mechanisms that underlie this change remain unclear. We have now generated mice that lack the lambda isoform of PKC in pancreatic beta cells (betaPKClambda(-/-) mice) and show that these animals manifest impaired glucose tolerance and hypoinsulinemia. Furthermore, insulin secretion in response to high concentrations of glucose was impaired, whereas the basal rate of insulin release wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 56 publications
1
49
1
Order By: Relevance
“…By contrast, exercise plays a crucial role in diabetic treatment, not only by lessening insulin resistance, but also through potentiating b-cell function and mass via enhancement of the insulin/IGF-I signaling cascade. Enhanced signaling promoted the expansion of b-cell mass by increasing hyperplasia via increased b-cell proliferation and decreased apoptosis (Hennige et al 2003, Hashimoto et al 2005. Thus, hyperplasia is necessary in order to strengthen b-cell function to compensate for insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, exercise plays a crucial role in diabetic treatment, not only by lessening insulin resistance, but also through potentiating b-cell function and mass via enhancement of the insulin/IGF-I signaling cascade. Enhanced signaling promoted the expansion of b-cell mass by increasing hyperplasia via increased b-cell proliferation and decreased apoptosis (Hennige et al 2003, Hashimoto et al 2005. Thus, hyperplasia is necessary in order to strengthen b-cell function to compensate for insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The area of ␤ cells was determined by hematoxylineosin staining of pancreatic sections as described previously (29).…”
Section: Methodsmentioning
confidence: 99%
“…The use of PKC inhibitors has resulted in conflicting conclusions (Jones and Persaud, 1998). Recent studies of PKC isoform-selective knock-out mice have indicated important roles for PKCδ and -λ in insulin secretion (Hashimoto et al, 2005;Uchida et al, 2007). Deletion of PKCε did not affect normal glucose-induced insulin secretion, but amplified that in islets treated with fatty acids (Schmitz-Peiffer et al, 2007).…”
Section: Pip 2 and Signalling Via Phospholipase Cmentioning
confidence: 99%